FAKTOR TEKNIS DALAM ALIH PENGGUNAAN LAHAN USAHATANI KAKAO MENJADI KELAPA SAWIT DI DESA MONDOKE KECAMATAN LAMBANDIA KABUPATEN KOLAKA TIMUR - Ardianti, Mirna Sri; Nikoyan, Anas; Arif, La Ode Kasno; Rosmawaty, Rosmawaty (Jurusan Penyuluhan Pertanian FP UHO, 2025)
The transition from cocoa farming to oil palm cultivation in Southeast Sulawesi, particularly in Mondoke Village, is attributable to technical factors. Oil palm is regarded as more lucrative, more manageable, and more resilient to pests and diseases than cocoa. The objective of this study is to ascertain the technical factors involved in the conversion of cocoa farming land to oil palm in Mandoke Village, Lambandia Subdistrict, East Kolaka Regency. The informants for this study consisted of farmers who were members of farmer groups and agricultural extension workers. The study's informant pool comprised a total of nine individuals, including eight farmers and one agricultural extension worker. The data collection techniques employed in this study encompassed observation, documentation, and interviews guided by a structured interview protocol. The present study centered on the technical factors that precipitated the conversion of agricultural land. The collected data was then subjected to qualitative analysis. The findings of the study indicate that the technical factors associated with the conversion of cocoa farmland to oil palm plantations, undertaken by farmers in Mondoke Village, are as follows: farmers possess the knowledge necessary for the cultivation of cocoa, yet they recognize that cocoa necessitates more intensive care than oil palms. Regular fertilization and pruning are essential to maintain the health of cocoa trees and prevent overgrowth, which can lead to increased susceptibility to pests such as PBK and Helopeltis. In contrast, oil palm maintenance is less complex, necessitating only the pruning of aged fronds to facilitate harvesting and deter pests. The management of pests, such as caterpillars and rats, in oil palm plantations can be effectively addressed through the implementation of controlled measures, including the application of pesticides and the maintenance of sanitation. Furthermore, the yield of old cocoa trees (over 20–25 years old) is lower, while oil palms demonstrate a longer and more stable production period throughout the year.